2020
DOI: 10.1002/ese3.602
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for sand control screen design of production wells for clayey silt hydrate reservoirs: A case study

Abstract: The process of extracting natural gas from gas hydrate‐bearing sediments (GHBS) may yield significant sand influx due to the metastable nature of GHBS. Selecting appropriate sand control media is vital to addressing the challenges caused by excessive sand production. This study proposes a protocol called holding coarse expelling fine particles (HCEFP) for sand control design. The protocol aims to provide a new optimization method for screen mesh size selection for clayey silt hydrate reservoirs. Detailed optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Larger production pressures, higher bottom-hole temperatures, larger horizontal stress differences, and higher permeabilities are deemed as causes for serious sand production . To improve the sand control efficacy, an optimization for the screen aperture size is needed as the screen should simultaneously retain coarse particles and avoid fine particle blockage . In addition, the dilatant behaviors under shearing in sediments with high hydrate saturations and low confining pressures can lead to tensile stresses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger production pressures, higher bottom-hole temperatures, larger horizontal stress differences, and higher permeabilities are deemed as causes for serious sand production . To improve the sand control efficacy, an optimization for the screen aperture size is needed as the screen should simultaneously retain coarse particles and avoid fine particle blockage . In addition, the dilatant behaviors under shearing in sediments with high hydrate saturations and low confining pressures can lead to tensile stresses.…”
Section: Introductionmentioning
confidence: 99%
“…24 To improve the sand control efficacy, an optimization for the screen aperture size is needed as the screen should simultaneously retain coarse particles and avoid fine particle blockage. 26 In addition, the dilatant behaviors under shearing in sediments with high hydrate saturations and low confining pressures can lead to tensile stresses. This is of particular significance as this phenomenon can contribute to unwanted hydrate dissociation in shallow methane hydrate reservoirs, and the geomechanical responses to methane hydrate exploitation can actually break the equilibrium in the hydrate-stable zones, 27,28 which may eventually evolve into uncontrolled gas release, sea floor subsidence, and submarine landslide.…”
Section: Introductionmentioning
confidence: 99%
“…Depressurization is also restricted by potential geohazards such as severe sand production [14][15][16], wellbore instability [17], and deformation of the sediment [18,19]. These potential geohazards are mainly controlled by the mechanical properties of HBS [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al and Cao et al believe that the secondary formation of hydrates and clay accumulation on the sand control medium are the key to clogging [14,15]. They suggested that a sand-control gravel sizing method called "Holding Coarse Expelling Fine Particles (HCEFP)" and artificial interference of downhole temperature was proposed to tackle the problems caused by possible screen clogging [16,17]. Uchida et al establish thermohydromechanically coupled formulation to research the features of sand production in gas hydrate-bearing sediments.…”
Section: Introductionmentioning
confidence: 99%